2023
DOI: 10.51821/86.1.10885
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of a population visiting a patient-centered informative website about irritable bowel syndrome

Abstract: Background and aims: Irritable bowel syndrome (IBS) is a chronic disorder characterized by abdominal pain and an altered bowel habit. The aim of this study was to evaluate the characteristics of a population visiting a patient-centered informative website about IBS. Methods: Five digital surveys were used to assess the Rome IV criteria, red flag symptoms, healthcare use, psychological comorbidities, quality of life, symptom severity, diet, physical activity. Patients were divided into a Rome positive and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In this first issue of 2023, several manuscripts should catch your attention. Kathleen Van Malderen and colleagues from the team led by Prof. De Schepper, investigated the characteristics of patients who visited a patient-centered information website on irritable bowel syndrome (IBS) (7). They found that, even if most of these patients had visited a health care provider, about 43% did not think their physician took them seriously and 59% thought that the physician lacked knowledge on IBS.…”
mentioning
confidence: 99%
“…In this first issue of 2023, several manuscripts should catch your attention. Kathleen Van Malderen and colleagues from the team led by Prof. De Schepper, investigated the characteristics of patients who visited a patient-centered information website on irritable bowel syndrome (IBS) (7). They found that, even if most of these patients had visited a health care provider, about 43% did not think their physician took them seriously and 59% thought that the physician lacked knowledge on IBS.…”
mentioning
confidence: 99%